2017
DOI: 10.1007/s10195-017-0456-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lower limb kinetics during gait, sprint and hop tests before and after anterior cruciate ligament reconstruction

Abstract: BackgroundThe purpose of this study was to evaluate the functional status prior to and at different times after anterior cruciate ligament reconstruction (ACLR), and to analyze the changes in the kinetic patterns of the involved and uninvolved lower limb during gait, sprint and three hop tests.Materials and methodsSeventy-four male patients with an ACL injury were included in the study. All patients performed a standardized kinetic protocol including gait, sprint and three hop tests (single-leg hop, drop verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…The full texts of 60 articles were assessed for eligibility according to the inclusion/exclusion criteria. Finally, 19 articles25–43 met the inclusion criteria of the present review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full texts of 60 articles were assessed for eligibility according to the inclusion/exclusion criteria. Finally, 19 articles25–43 met the inclusion criteria of the present review (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of the 19 included studies had a cross-sectional design25–32 34–43 and one had a prospective design 33. A total of 624 ACLR patients (424 men, 200 women; mean age 30 years) as well as 315 controls (208 men, 107 women; mean age 27.6 years) were included in the review (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The biomechanical findings during landing in the current study are also consistent with previous work that assessed 1-year longitudinal changes in peak ipsilateral VGRF of patients with ACLR during a drop jump task. 29 At 3 years, the patients with ACLR exhibited similar peak VGRF and KFM Figure 3. (A) Correlation between peak vertical ground-reaction force (VGRF) at 6 months and change in T1r value in the posterior horn of the medial meniscus (PHMED) from 6 months to 3 years in the anterior cruciate ligament reconstruction (ACLR) cohort.…”
Section: Discussionmentioning
confidence: 89%
“…Each person has his/her own inherent pattern for walking, using different postural, neuromuscular, locomotor, and dynamic balance control. Some studies [44][45][46] showed there were different patterns for healthy people and many others differed under some pathological condition. Moreover, these patterns depended on external parameters such as velocity and contact surfaces.…”
Section: Discussionmentioning
confidence: 99%